The Role of Primary Health Care Toward Healthy Aging - Dhanasari Vidiawati; Yuda Turana; Tonny Sundjaya (Amerta Nutrition, 2020)
Background: According to the World Health Organization, healthy aging is the process of developing and maintaining functional abilities that make the elderly happy. The increase in the elderly population requires more attention. In particular, health services at the primary health care level face problems related to the limited capacity of overall health services, especially in terms of health promotion and preventive health issues. It is necessary to improve the quality of health care services for the elderly to prevent greater health problems among the elderly population.Objectives: Understand the need to provide holistic health services for healthy aging and use their capabilities, and strengthen cooperation among health professionals in achieving healthy aging.Discusion: Primary health care is pointed out that primary health care should provide comprehensive services in a holistic manner to support a healthy aging process. Therefore, a well-structured, integrated, and cross-industry collaborative primary care system is needed. The system should include changes in professional behavior, coordination of care, and participation of patients' families and communities in comprehensive health care. This can be achieved through inter-professional education, continuous training and education of primary health care professionals, as well as primary health care services and cross-level health care technology innovation.Conclusions: Healthy aging is not just the absence of disease. Everyone in health and social care at all levels can play a role to help improve healthy aging. To make the elderly healthy, starting from the prevention of young health problems, it requires collaboration between health workers, primary health care and other health service levels, and health care that cooperates with patients, families, and communities.Keywords: healthy aging, primary care, preventive, health worker